How true is the truth? A study of the factors affecting honest response behaviour of patients in hospital settings - Mushtaq Ahmad Darzi; Sheikh Basharul Islam; Suhail Ahmad Bhat; Syed Owais Khursheed (Rajagiri Management Journal, 2024)
Purpose – The current study is aimed at identifying the prominent influencers that affect the response behaviour of patients in a hospital environment. Design/methodology/approach – The research is based on the data collected through the participant observation method while interviewing patients about the quality of healthcare services in nine community health centres of the Kashmir division. Thematic analysis was performed on the information collected from patients admitted to various hospital sections. Findings – The analysis of the qualitative data revealed that the presence of hospital staff near respondents, perceived risk of maltreatment, social desirability, the sensitivity of the topic, risk of information sharing and attitude towards surveys are the most frequently observed factors that modulate the patient's tendency to truthfully report critical facts about the problem understudy. Originality/value – These results can help researchers to exercise caution while communicating with respondents and collecting data related to serious issues in a natural setting.